(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
In the "Presidente Sarmiento" Provincial Park (PPPS) studies have been carried out on herpetofauna and avifauna, but there are no studies on mammals. The objective of this note is to report for the first time the presence of Leopardus geoffroyi in the PPPS.